Diurnal variability of water temperature, pH and DO in the underground type fish shelter - Hyuk Ahn, Chang; Lee, Saeromi; Myeon Song, Ho; Chul Joo, Jin; Roh Park, Jae (Scientific Journal of Environmental Sciences, 2016)
We newly developed artificial deep pool (ADP) that secures a shelter and habitat space in bottom of the pond for fish escape from unfavorable conditions in freshwater ecosystem. Because the ADP is an underground structure, we were compared by measuring the diurnal basic water quality (water temperature, pH, DO saturation) in St. 1 (open water) and St. 2 (inside of ADP) in shallow small pond for a year. In result, ADP provides constant optimal temperatures and DO level to help fish survival in extreme water environment conditions. Therefore, ADP is able to reduce thermal stress in the hot season, and to minimize energy expenditure in the cold season for freshwater fish. If the ADP will be introduced in shallow ponds it will be able to significantly increase the fish survival during the year.